The educational system of Yakutia: overcoming the challenges - V. M. Savvinov (Вестник Северо-Кавказского федерального университета)
Introduction. The scale of the territory of Russia, the heterogeneity of its landscapes, the diversity of culture and peoples’ traditions of multinational country, and the peculiarities of the socio-economic development of the regions determine the relevance of the problem of understanding the environmental influence on the development of regional and territorial educational systems. The severity of the problem is most clearly expressed in conditions of growing environmental uncertainty and dynamic geopolitical changes in the world. Goal. Identification of the specifics of the regional education system of the Republic of Sakha (Yakutia), its personnel, scientific reserves, potential growth opportunities and problems associated with environmental factors. Materials and methods. The study is based on the analysis of the Yakutsk master plan, materials from strategic sessions and expert discussions on the priorities for the development of education in the Far East, held in 2021–2023. Results and Discussion. It was revealed that environmental factors determine the diversity of development models of territorial and regional educational systems. In the context of the formation of a sovereign education system in Russia, strengthening the independence of educational organizations, and growing public demand for systemic changes in education, the relevance of taking into account external factors in managing the development of education increases significantly. Conclusion. Based on the results of the study, it was concluded that managing the development of the regional educational system involves solving a set of interrelated tasks aimed at reducing barriers to access to education, transitioning from a strategy of local changes to systemic transformations built on a program basis.